2022
DOI: 10.3389/fnut.2022.850103
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Biochemical Evaluation of Amorphous Solid Dispersion of Naringenin Prepared Using Hot-Melt Extrusion

Abstract: Naringenin (NRG) is a plant-derived flavonoid. Due to its antioxidant, anti-inflammatory, and analgesic activities it is beneficial to human health and is often used as a functional food ingredient; however, it has poor water solubility and low in vivo bioavailability. Therefore, the efficacy of NRG can be improved by enhancing its water solubility to increase gastrointestinal absorption. Conventional methods for the formulation of NRG are very complex and use toxic organic solvents, making them impractical fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The amorphous state of polyphenols is most often stabilized by hydrogen bonds. Recent work shows the amorphous solid dispersion of such polyphenols as quercetin [11,16,17], resveratrol [18], curcumin [18][19][20], naringenin [21], daidzein [22], and genistein [23]. The amorphous form of pterostilbene was obtained, for example, by Tzeng et al via nanoprecipitation with Eudragit ® e100 and polyvinyl alcohol (PVA) [24].…”
Section: Introductionmentioning
confidence: 99%
“…The amorphous state of polyphenols is most often stabilized by hydrogen bonds. Recent work shows the amorphous solid dispersion of such polyphenols as quercetin [11,16,17], resveratrol [18], curcumin [18][19][20], naringenin [21], daidzein [22], and genistein [23]. The amorphous form of pterostilbene was obtained, for example, by Tzeng et al via nanoprecipitation with Eudragit ® e100 and polyvinyl alcohol (PVA) [24].…”
Section: Introductionmentioning
confidence: 99%
“…These methods allow for achieving a molecularlevel dispersion of polyphenols within the matrix, creating a highly homogeneous and amorphous system. In recent years, it has been demonstrated that compounds such as sinapic acid [18], resveratrol [17], pterostilbene [10], curcumin [17,20,21], hesperidin [9,22], daidzein [16], genistein [19,23], hesperetin [12,22], naringenin [24], and quercetin [25][26][27] can be can be formulated using ASD. To date, no ASDs of KMP have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Female BALB/c mice were obtained from Japan SLC Inc. (Shizuoka, Japan) and acclimatized under controlled environmental conditions (22 ± 1°C; 50% ± 10% relative humidity; 12-h light-dark cycle; lights on at 08:00 AM) for some days before the start of the experiment. All animals were fed with normal powdered food (MF, Oriental Yeast Co. Ltd., Tokyo, Japan) and had ad libitum access to water [18]. TFM, TFM-lc, and TF1 were each prepared by mixing with powdered food at a concentration of 0.02-0.20% and administration was started 2 weeks prior to OVA sensitization.…”
Section: Animalsmentioning
confidence: 99%